Chiral-based mechanical metamaterial with tunable normal-strain shear coupling effect. (1st June 2023) - Fleisch, Mathias; Thalhamer, Andreas; Meier, Gerald; Huber, Philipp Arno Franz; Fuchs, Peter Filipp; Pinter, Gerald; Schlögl, Sandra; Berer, Michael
Highlights: A mechanical metamaterial with tunable normal-strain shear coupling is presented. A few geometric parameters allow for shear coupling in a broad range. The three-dimensional design allows for spatial positioning with one-dimensional strain. Abstract: Different designs for mechanical metamaterials with tunable normal-strain shear coupling effect have been demonstrated over the last years. Their adjustable shear deformation makes them suitable as building blocks for soft robotics applications or structures with a desired deformation behavior, such as shape morphing structures. Herein, we present a modified 2.5D and 3D chiral-based mechanical metamaterials with tunable normal-strain shear coupling effect and Poisson's Ratios close to zero. Advancing from conventional chiral-based metamaterials by introducing additional geometric freedoms into the design of the unit cell, a broad range of shear deformations, compression moduli and porosities can be achieved. 2.5D specimens with selected geometric parameters were additively manufactured with polypropylene using Fused Filament Fabrication. Compression tests were performed to investigate the mechanical properties and shear deformation. Two different numerical models were employed using ABAQUS to study the influence of the geometric parameters onto the mechanical properties and were verified by the experiments. The numerical material models were based on three-point-bending test data. The three-dimensional design was investigated with numerical simulations based on a homogenization approach to cover a broad range of geometric parameters.